Meningkatkan Efisiensi Operasional dan Pelayanan kepada Pelanggan bagi UMKM Laundry WisRuesik - Santoso, Bambang; Octaviano, Alvino; Sofiana, Sofa (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service activity took place at WisRuesik Laundry, a laundry service company that provides laundry services for clothes and other items. The types of items accepted vary from clothing, carpets, shoes, bags, dolls, bed sheets, and more. Regular and express services are available, where time determines the price. Manual transaction recording is a challenge for WisRuesik Laundry. Transactions are often miscalculated and inaccurate, daily and weekly reports take a long time to produce, customers do not have access to the status of their laundry, and the cashiers at the front desk need to carefully calculate the prices and the changes. The Community Service Team created an application to help the company overcome these obstacles. Needs analysis, system design, program development, writing a user manual, training, and mentoring were the methods chosen. As a result, transactions can be faster and more accurate, customers can view transaction status from the web, and managers can monitor transactions more easily.